2020
DOI: 10.1177/0003134820964495
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Endoscopic Stent in Management of Postesophagectomy Leaks

Abstract: Introduction Anastomotic leak is a dreaded complication following esophagectomy. Conventional management for leaks includes invasive reoperation and even gastrointestinal diversion. Objective The aim of this study was to examine our contemporary outcome of using endoscopic esophageal stenting as primary therapy for management of anastomotic leak following minimally invasive esophagectomy (MIE). Methods We reviewed data on 11 patients who developed an esophageal leak following 111 MIE between January 2011 and D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 15 publications
0
11
0
2
Order By: Relevance
“…Several supportive advances have improved the management of postoperative anastomotic leaks after an esophagectomy (eg, enhanced critical care, earlier diagnosis, interventional radiology-placed drains, endoscopically placed stents, endoscopic vacuum therapy). [118][119][120] However, management of an intrathoracic leak remains challenging and often determines severe morbidity with high associated mortality. In fact, our study showed higher rates of overall morbidity, severe morbidity, and mortality with the use HS anastomosis, which might be explained by the significantly higher incidence of anastomotic leakage in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several supportive advances have improved the management of postoperative anastomotic leaks after an esophagectomy (eg, enhanced critical care, earlier diagnosis, interventional radiology-placed drains, endoscopically placed stents, endoscopic vacuum therapy). [118][119][120] However, management of an intrathoracic leak remains challenging and often determines severe morbidity with high associated mortality. In fact, our study showed higher rates of overall morbidity, severe morbidity, and mortality with the use HS anastomosis, which might be explained by the significantly higher incidence of anastomotic leakage in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Several supportive advances have improved the management of postoperative anastomotic leaks after an esophagectomy (eg, enhanced critical care, earlier diagnosis, interventional radiology–placed drains, endoscopically placed stents, endoscopic vacuum therapy) 118–120. However, management of an intrathoracic leak remains challenging and often determines severe morbidity with high associated mortality.…”
Section: Discussionmentioning
confidence: 99%
“…Management of the leak depends largely on the location. A post-esophagectomy cervical leak usually benefits from simple neck drainage and wound care [ 9 ]. The intrathoracic or intra-abdominal leak is more complex and treatment options vary from conservative treatment to surgical reintervention, depending on several factors, including the patient’s clinical condition, size of the leak, and timing since surgery [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…El drenaje adecuado, la reintervención con colgajos pleurales o diafragmáticos y la derivación (esofagostomía) son opciones de tratamiento para las fugas graves no controladas. Recientemente, se ha despertado el interés por las opciones mínimamente invasivas para tratar las fugas anastomóticas (4) , incluida la colocación de endoprótesis esofágicas, que han demostrado ser eficaces en el tratamiento inicial de las fugas anastomóticas esofágicas y pueden ofrecer comorbilidades bajas, con resultados comparables a las de otros tratamientos (5)(6)(7)(8)(9) .…”
unclassified
“…El tipo de endoprótesis y el método de colocación pueden variar debido a la disponibilidad local, las preferencias del médico y las características del paciente, lo que puede contribuir a los diferentes riesgos de complicación. Se cree que hay varios factores que contribuyen al fracaso de la endoprótesis, como una mala selección del paciente, un diámetro incorrecto de la endoprótesis, una mayor duración de la estancia de la endoprótesis, una actividad funcional baja antes de la cirugía, el desarrollo de una fístula esofágica, la exposición previa a la quimioterapia, el retraso en el diagnóstico de la fuga 48 horas después de producirse, una mayor edad, el aumento del tamaño de la fístula y las comorbilidades graves (6,7,9) . En este número se presenta el estudio de Ovalle y colaboradores, de carácter unicéntrico y retrospectivo, quienes durante 11 años estudiaron a 11 pacientes con fugas anastomóticas esofagogástricas posquirúrgicas a quienes se les colocó 14 stents y se evaluaron los desenlaces técnicos y clínicos.…”
unclassified